2014
DOI: 10.1111/acel.12205
|View full text |Cite
|
Sign up to set email alerts
|

Lifelong treatment with atenolol decreases membrane fatty acid unsaturation and oxidative stress in heart and skeletal muscle mitochondria and improves immunity and behavior, without changing mice longevity

Abstract: The membrane fatty acid unsaturation hypothesis of aging and longevity is experimentally tested for the first time in mammals. Lifelong treatment of mice with the β1-blocker atenolol increased the amount of the extracellular-signal-regulated kinase signaling protein and successfully decreased one of the two traits appropriately correlating with animal longevity, the membrane fatty acid unsaturation degree of cardiac and skeletal muscle mitochondria, changing their lipid profile toward that present in much more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 41 publications
0
19
1
Order By: Relevance
“…Activation of the Raf-ERK-MAPK has been described in long-lived mutant mice (Yan et al 2007) and in DR in rat heart (Castello et al 2011). Furthermore, ERK activation has been related to decreases in lipid-derived oxidative stress (Gómez et al 2014). However, in the present investigation no variations in ERK phosphorylation were observed in any group.…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…Activation of the Raf-ERK-MAPK has been described in long-lived mutant mice (Yan et al 2007) and in DR in rat heart (Castello et al 2011). Furthermore, ERK activation has been related to decreases in lipid-derived oxidative stress (Gómez et al 2014). However, in the present investigation no variations in ERK phosphorylation were observed in any group.…”
Section: Discussioncontrasting
confidence: 57%
“…Inhibition of mTOR is documented in mammalian DR models (Wei et al 2013;Johnson et al 2015). ERK activation has been described in long-lived mutant mice (Yan et al 2007) and in DR in rats (Castello et al 2011) and has been recently related to decreases in oxidative stress (Gómez et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, treatment with atenolol, a β1-adrenergic receptor blocker, decreased unsaturation index in mice, but did not lead to a significant difference in longevity (Gómez et al, 2014). Atenolol treatment did, however, decrease oxidative damage and improved age-related behavioral functions, such as motor coordination, so the lack of longevity increase was likely related to decreases in heart rate and increases in arterial pressure variation, similar to results from an analogous study (Spindler et al, 2013;Gómez et al, 2014). In addition to the problems listed above with specific studies, some studies may not have found correlations between peroxidation index and longevity because of individuals that were not of equivalent ages, as fatty acyl composition changes with age (Hulbert, 2005).…”
Section: Membrane Pacemaker Hypothesis Of Agingmentioning
confidence: 92%
“…Queen bees, which live an order of magnitude longer than workers, had a lower peroxidation index than did worker bees (Haddad et al, 2007). Finally, in many cases, higher peroxidation index and shorter lifespan were predictive of higher oxidative damage to lipids, DNA, and proteins (Aguilar-Toral et al, 2014;Gómez et al, 2014;Jeon et al, 2001;Pamplona et al, 1999aPamplona et al, , 1999cPamplona et al, , 1996.…”
Section: Membrane Pacemaker Hypothesis Of Agingmentioning
confidence: 95%
See 1 more Smart Citation